PENGGUNAAN MODEL INKUIRI TERBIMBING BERBASIS MULTI MEDIA UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR FISIKA SISWA KELAS X MIPA-2 MAN 15 JAKARTA - Intan Irawati (Balai Diklat Keagamaan Jakarta, 2020)
The research objectives are to increase of the activity of and physics’ accomplishments of students in grade X Science-2 by guided inquiry learning based multimedia. The research was being conducted in the second semester of 2016-2017. Research method that was used is Classroom Action Research (CAR) that was undertaken in two cycles and two sessions in every cycle. Each cycle consisting of the stages planning, action, observation and relection. The research instruments were to identify students observation in the groups, sheets of observation of students in the teaching and learning activities, sheets of of the observation of the activity of the teacher in the teaching and learning activities, and the instrument of the physics test of a momentum and impulses . Learning physics by guided inquiry learning based multimedia had increased the activity of students in teaching and learning activities of the average score 71.8 to 85. Students became more active in noting a lesson, analyzed problems, to act critical and argue in scientific terms. The application of guided inquiry learning based multimedia had improved the ability of achievements physics students from the average score 71,7 to 84 on first cycle and be 93 in second cycle.